Evolutionary innovations through gain and loss of genes in the ectomycorrhizal Boletales. Issue 3 (9th December 2021) - Wu, Gang; Miyauchi, Shingo; Morin, Emmanuelle; Kuo, Alan; Drula, Elodie; Varga, Torda; Kohler, Annegret; Feng, Bang; Cao, Yang; Lipzen, Anna; Daum, Christopher; Hundley, Hope; et al.
Summary: We aimed to identify genomic traits of transitions to ectomycorrhizal ecology within the Boletales by comparing the genomes of 21 symbiotrophic species with their saprotrophic brown‐rot relatives. Gene duplication rate is constant along the backbone of Boletales phylogeny with large loss events in several lineages, while gene family expansion sharply increased in the late Miocene, mostly in the Boletaceae. Ectomycorrhizal Boletales have a reduced set of plant cell‐wall‐degrading enzymes (PCWDEs) compared with their brown‐rot relatives. However, the various lineages retain distinct sets of PCWDEs, suggesting that, over their evolutionary history, symbiotic Boletales have become functionally diverse. A smaller PCWDE repertoire was found in Sclerodermatineae. The gene repertoire of several lignocellulose oxidoreductases (e.g. laccases) is similar in brown‐rot and ectomycorrhizal species, suggesting that symbiotic Boletales are capable of mild lignocellulose decomposition. Transposable element (TE) proliferation contributed to the higher evolutionary rate of genes encoding effector‐like small secreted proteins, proteases, and lipases. On the other hand, we showed that the loss of secreted CAZymes was not related to TE activity but to DNA decay. This study provides novel insights on our understanding of the mechanisms influencing the evolutionary diversification of symbiotic boletes.